Freedom of Navigation Operations: Better Quiet Resolve - Chong, Ja Ian (2015)
Highly publicised American FONOPs makes it more challenging for many Southeast Asian governments to openly welcome such action. A more preferable approach may be consistent, regular, but quiet FONOPs by the US to avoid a premature raising of stakes.